Risk assessment models and early warning systems - Peter Brecke (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
This paper addresses model design and data-related issues pertaining to the use of risk assessment models in support of conflict early warning systems. The paper first examines the data needed for risk assessment models. It argues that there are actually two types of data that we must collect and use: data to determine the theories that best explain the outbreak or escalation of violent conflict and data corresponding to variables that have been demonstrated to have predictive power and thus are appropriate for use in a risk assessment model. With respect to intrastate conflicts there remains a dearth of data of the first type that is only slowly being corrected. Collecting data of the second type will continue to be an inefficient process until better theories have been formulated and tested with the first type of data. The paper then examines a number of models germane to risk assessment and conflict early warning. It finds that except for one class of models, so-called correlational models, there has been only limited work done even though the alternatives appear to have promise. – – Das Papier behandelt Modellierungsfragen und Datenprobleme bezüglich der Zweckmäßigkeit sog. risk-assessment-Modelle bzw. zur Klärung von Frühwarnmodellen. Zunächst wird generell die Datenlage überprüft. Dabei läßt sich argumentieren, daß zwei Typen von Daten im Mittelpunkt stehen: einerseits Daten, die zur Erklärung des Auftretens und der Eskalation von gewaltsamen Konflikten herangezogen werden können, andererseits Daten, die sich für die Fundierung von risk-assessment-Modellen eignen. Während beim ersten Typus vor allem ein eklatanter Mangel bezüglich innerstaatlicher Konflikte herrscht, sind wir beim zweiten Typ mit dem Problem konfrontiert, daß das Generieren von immer neuen Daten solange ein wirkungsloses Unterfangen bleiben wird, wie es nicht mehr theoretische Klarheit über die Prozeß- und Strukturbedingungen von Gewalt gibt. Anschließend werden noch zentrale Modelle überprüft, die sich mit dem risk-assessment und der Frühwarnung befassen. Es wird gezeigt, daß – mit Ausnahme von Korrelationsmodellierungen – noch immer zuwenig Arbeit investiert wird, wenngleich die Alternativen durchaus vielversprechend sind.
Keywords: 320